Surviving solitary : living and working in restricted housing units - Rudes, Danielle S. (Danielle Sheldon), 1971- (Stanford University Press, 2022)
"Surviving Solitary offers a unique, first-hand, narrative perspective from both inmates living and staff working within restricted housing units (RHUs) in seven U.S. prisons. Using data collected over two years within RHUs in both men's and women's prisons within the Pennsylvania Department of Corrections, this manuscript will cover five critical topics at the forefront of current policy and practice within carceral spaces: Risk, Rules, Relationships, Reform and Reentry. Rudes will juxtapose inmate and staff perspectives and experiences in every substantive chapter highlighting the intense and often overlooked similarities and differences between and among individuals on both sides of the bars. This manuscript aims to pull back the curtain on an area of carceral punishment vastly misunderstood and where intimate knowledge is significantly lacking. While RHUs are ostensibly designed to punish, control, contain, and in some cases remedy behavior of inmates, Rudes finds that they are fundamentally inadequate for dealing with the complex social and psychological harms that they also cause. The focus of this book is on exposing these harms and the ways that they are woven into the fabric of daily life for both staff and inmates, rendering any possible benefit of the RHUs meaningless. This carries critical consequences for residents released back into the general population or to the community, as their time in restricted housing units may impair their ability to understand and navigate social life on the outside, making prison a place for criminogenic increase rather than a locale for deterring future crime, repairing harms, and/or rehabilitating. For staff, time spent in restricted housing units is akin to doing time themselves. Staff working here often report feeling little/no job satisfaction, daily stress and fear, anomie regarding rules/regulations, and trouble forming relationships. The long-term effect of these conditions, the book will argue, greatly interferes with their ability to do their jobs and maintain wellness in daily life. The book will conclude with some important policy recommendations for changes in RHUs that vastly improve the current conditions"--